BIPOLARITY IN UNDERSTANDING THE GENESIS OF THE SPORTIZATION PHENOMENON - Lubysheva, L.I. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to substantiate the bipolarity of the genesis of the development of the phenomenon of sportization from the standpoint of the historical context. Results and conclusions. Sport and physical culture as two social phenomena have gone through a complex historical path of development from bodily-motor practices to a modern social institution, creating a dualistic nature of sportization. Following the philosophical paradigm of the bipolarity of any phenomenon, modern sportization is realized, on the one hand, using the potential of the historical genesis of this phenomenon, on the other hand, subject to the adaptation of conversion technologies to the new conditions of sports activity based on the preservation of its internal mechanisms and the evolution of the means and methods used throughout over the course of its development. Introduction. Sport is an important part of the general culture of society, its natural phenomenon, inherent in social life and inseparable from it.